2015
DOI: 10.4028/www.scientific.net/msf.827.326
|View full text |Cite
|
Sign up to set email alerts
|

Study of Alkalization to the Crystallinity and the Thermal Behavior of Arenga Pinnata “Ijuk” Fibers-Based Polylactic Acid (PLA) Biocomposite

Abstract: The pollution due to non-degradable material such as plastics, has led to studies about the development of environmental-friendly materials. Because of natural sources-based materials and their biodegradability, polylactid acid (PLA) and ijuk fiber are interesting to be modified into a composite. Furthermore this study is also expected to reduce the impact of environmental problems. Surface modification of ijuk fiber through alkalinization, was aimed to enhance compatibility between the ijuk fiber and the PLA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…[5] On the other hand, Luduena et al studied the influence of lignocellulosic filler to the crystallization behaviour of polycaprolactane. [6] Furthermore, study of crystallization behaviour of "ijuk" fibre based polylactic acid biocomposite has been done by Chalid et al [7] It is indicated that natural fibres can act as heterogenous nucleating agents which change the morphology and crystallinity of the interface region. [6] Moreover, through this research, "ijuk" fibre is able to be a novel approach for pp nucleating agent as well as existing pp nucleating agent such as sorbitol derivated and modified CaCO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[5] On the other hand, Luduena et al studied the influence of lignocellulosic filler to the crystallization behaviour of polycaprolactane. [6] Furthermore, study of crystallization behaviour of "ijuk" fibre based polylactic acid biocomposite has been done by Chalid et al [7] It is indicated that natural fibres can act as heterogenous nucleating agents which change the morphology and crystallinity of the interface region. [6] Moreover, through this research, "ijuk" fibre is able to be a novel approach for pp nucleating agent as well as existing pp nucleating agent such as sorbitol derivated and modified CaCO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…This target has been driven by finding applications of MFC in material engineering. The inherent stiffness and high degree of crystallinity make it ideally suited for reinforcing and load bearing application in composite …”
Section: Introductionmentioning
confidence: 99%
“…It takes only 3‐5 months for the sweet sorghum to mature and the species can be planted in very dry area . Sorghum is one of important renewable natural resource that has not been well investigated yet . Previous researches reported that natural fiber like flax, hemp, jute, and sisal have been well confirmed as good potential reinforcement for composite .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations